Ultracold molecules and ultracold chemistry - Bell, M; Softley, T (2009)
The recent development of a range of new methods for producing samples of gas-phase molecules that are translationally cold ([image omitted] K) or ultracold ([image omitted] mK) is driving efforts to study reactive and inelastic collisional processes in these temperature regimes. In this review article the new methods for cold/ultracold molecule production are reviewed in the context of their potential or current use in collisional studies and progress in the application of these methods is highlighted. In these sub-Kelvin temperature ranges, where the de Broglie wavelength is long compared with molecular dimensions, quantum effects may play a crucial role in the collision dynamics. Reactions with no potential energy barrier are of greatest importance, and this review article summarizes some of the principal theoretical approaches to understanding quantum effects in these barrierless processes.